Social and Virtual Segregation: A Study of Gated Communities in Yogyakarta - Artosa, Odam Asdi; Dewi, Novi Paramita; Yuliarso, Kurniawan Yanto; Ambardi, Kuskridho (UI Scholars Hub, 2022)
The problem of social segregation gains new relevance as digital technology has now become the core of people’s lives and work. Unfortunately, this factor is often neglected in studies of social segregation. Previous studies have only taken note of social and spatial segregation. This study aims to fill a conceptual gap by raising the virtual dimension within socio-spatial segregation. This research finds that virtual segregation has strengthened segregationist tendencies that follow the growth of luxurious housing complexes and gated communities. Furthermore, this study also asserts that deregulation policies in housing and the commercial development of telecommunication infrastructure are factors that exacerbate the tendency of social segregation. Although communities may currently find segregation to be socially acceptable, in the long run, this tendency will complicate efforts to strengthen social cohesion and may intensify socio-economic problems across the population . Focusing on the case of Yogyakarta, this study employs a combination of methods for collecting data that include secondary data analysis, interviews, and Focus Group Discussions.